Ideologías lingüísticas, bilingüismo y español como lengua de herencia en Europa = Linguistic ideologies, bilingualism, and Spanish as a heritage language in Europe - Moreno Fernández, Francisco; Álvarez Mella, Héctor; Elizondo Romo, Mariel (Círculo de lingüística aplicada a la comunicación, 2025)
The article explores the different discourses about bilingualism and heritage language produced by early bilingual education initiatives. More concretely, recurring beliefs, ideas, and conceptualizations that circulate about bilingualism and Spanish as a heritage language in bilingual education spaces of different European countries are analyzed. Empirical analyses are oriented towards three research questions: 1) what are the main ideologies about bilingualism and heritage language circulating discourses of education initiatives; 2) what are their main discursive expressions; and 3) how do they discursively interrelate. The results show how the early bilingual education spaces are presented through a purist idea of bilingualism, a cosmopolitan image of bilingual education, and a vision of Spanish oriented to the culture and identity dimensions of heritage language.